2015
DOI: 10.1634/theoncologist.2015-0175
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous B-Cell Lymphoma: Management and Patterns of Recurrence at the Multimodality Cutaneous Lymphoma Clinic of The Ohio State University

Abstract: Background. The increasing incidence of primary cutaneous B-cell lymphomas (PCBCLs) presents new challenges for clinicians. Despite advances in the clinical and pathologic characterization of PCBCL, the significance of the current staging approach as a risk profiling tool and the effect of various treatments on outcome remain unclear. Materials and Methods. We retrospectively reviewed patients who presented with a diagnosis of PCBCL seen at The Ohio State University between 1998 and 2012. We reviewed the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…Considering the clinical presentation, most of the herein analyzed cases presented as localized processes, in which a sparse local clonal plasmacytic infiltration causes a localized amyloid deposition within the tissue in an otherwise healthy patient without overt lymphoma. The final classification as a localized disease is solely possible ruling out a secondary infiltration by an underlying systemic plasmacytic-differentiated B cell lymphoma by appropriate staging as proposed for comparable entities like primary cutaneous lymphomas [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the clinical presentation, most of the herein analyzed cases presented as localized processes, in which a sparse local clonal plasmacytic infiltration causes a localized amyloid deposition within the tissue in an otherwise healthy patient without overt lymphoma. The final classification as a localized disease is solely possible ruling out a secondary infiltration by an underlying systemic plasmacytic-differentiated B cell lymphoma by appropriate staging as proposed for comparable entities like primary cutaneous lymphomas [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor , Primary cutaneous B‐cell lymphomas (PCBCLs) are a heterogeneous group of extranodal lymphomas 1 . Primary cutaneous marginal zone lymphoma (MZL) and follicle centre lymphoma (FCL), the most prevalent PCBCLs, are typically indolent.…”
Section: Patient Id Diagnosis Previous Therapy Location No Of Lesionmentioning
confidence: 99%
“…Locoregional nodal extension does not impair prognosis of primary cutaneous anaplastic lymphomas DOI: 10.1111/bjd.19495 DEAR EDITOR, Primary cutaneous anaplastic lymphomas (pcALCLs) commonly present as solitary or grouped skin lesions and have a 5-year specific survival greater than 91%. [1][2][3] One study showed that, in cases of extracutaneous extension, 5-year overall survival (OS) is 41%. 4 At diagnosis some patients have skin and locoregional node involvement, but their prognosis is as favourable as that of patients with lesions limited to the skin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Первичные лимфомы кожи (ПЛК) представляют собой гетерогенную группу заболеваний, развитие которых обусловлено неопластической пролиферацией в коже клонов Т-лимфоцитов, NK-клеток или В-лимфоцитов, аффинных к кожной ткани. По данным литературы [1][2][3], заболеваемость первичными кожными лимфомами в мире варьирует от 0,3 до 1,18 случаев на 100 тыс. населения и продолжает увеличиваться.…”
Section: в помощь практическому врачуunclassified